Intermetallic Compounds Formation and Applications - Aliofkhazraei, Mahmood (IntechOpen, 2018)
Intermetallic compounds are usually brittle with high melting points. Their properties are often found among ceramic and metallic materials. In most cases, their hot corrosion resistance and simultaneously hardness are important. One of the main applications of intermetallic compounds is for superalloy turbine blades in which they show appropriate high-temperature-related properties. This book collects new developments about intermetallic compounds and their recent usages.